Clinical value of lncRNA TUG1 in temporal lobe epilepsy and its role in the proliferation of hippocampus neuron via sponging miR-199a-3p. Issue 2 (20th December 2021) - Li, Chunlian; Zheng, Xiaojing; Liu, Pingping; Li, Meilian
ABSTRACT: Temporal lobe epilepsy (TLE) often occurs in childhood and is the most common type of epilepsy. Studies have confirmed that long non-coding RNAs (lncRNAs) can affect the progression of neurological diseases. This study explored the expression level of lncRNA TUG1 in TLE children and its clinical significance and investigated its role in hippocampal neurons. 86 healthy individuals and 88 TLE children were recruited. The expressions of lncRNA TUG1 and miR-199a-3p in serum were detected by qRT-PCR. Hippocampal neurons were treated with non-Mg 2+ to establish TLE cell model. MTT assay and flow cytometry assay was used to detect the effect of lncRNA TUG1 on the proliferation and apoptosis of hippocampal neurons. A dual-luciferase reporter assay was done to confirm the target relationship. The expression of lncRNA TUG1 was increased in TLE children compared with the control group. The diagnostic potential was reflected by the receiver operator characteristic (ROC) curve, with the AUC of 0.915 at the cutoff value of 1.256. Elevated levels of TUG1 were detected in TLE cell models, and TUG1 knockout could enhance cell activity and inhibit cell apoptosis. MiR-199a-3p was the target of TUG1. Clinically, the serum miR-199a-3p levels showed a negative association with TUG1. LncRNA TUG1 may be a biomarker of TLE diagnosis in children, and can regulate hippocampal neuron cell activity and apoptosis via sponging miR-199a-3p.